The Development and Psychometric Analysis of The Social Media Engagement Adolescent Scale (SMEAS) in Indonesia - Rizqa Nur Fajar; Dewi Maulina; Farah Almira Nu'ma; Nadatuljannah Alza; Nurani Fitriyah; Raudhah Mutiara Riyandra (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
This study aims to develop a Social Media Engagement Adolescent Scale (SMEAS) that can comprehensively capture the culture of social media use among Indonesian adolescents and its implications for educational psychology. This study employs a quantitative approach and uses self-report for data collection. A total of 435 participants aged between 17-21 years were involved in this study, and the data were analyzed using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). The results of this study showed that the validated Social Media Engagement Adolescent Scale (SMEAS) consists of 24 statement items divided into three dimensions: affective engagement, behavioral engagement, and cognitive engagement based on social media engagement theory from Ni et al. Reliability testing using Cronbach’s α showed that each dimension in SMEAS has good reliability. Item discrimination analysis revealed that all items in SMEAS could differentiate individuals with high and low levels of engagement. Based on the results, SMEAS can be considered a reliable and valid scale for measuring Social Media Engagement among adolescents in Indonesia.